2016
DOI: 10.1039/c5ra24742j
|View full text |Cite
|
Sign up to set email alerts
|

Promotional effect of Fe on the performance of supported Cu catalyst for ambient pressure hydrogenation of furfural

Abstract: A noble-metal free FeCu based bimetallic catalyst system prepared by facile co-impregnation method was found to be a highly admirable for vapour phase selective hydrogenation of furfural to furfuryl alcohol at ambient pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 57 publications
2
62
0
Order By: Relevance
“…They got 51% of MF yield at 220 • C for 14 h under 90 bar of H 2 pressure (Table 1, entry 26). The promoting effect of Fe on Cu catalyst performance was also studied by Manikandan et al [136]. Cu-Fe/Al 2 O 3 catalyst, with 10 wt% of Fe, exhibited an excellent activity that led to high furfural conversion (>93%) and FA selectivity (>98%) under mild reaction conditions ( Table 1, entry 27).…”
Section: Introductionmentioning
confidence: 84%
“…They got 51% of MF yield at 220 • C for 14 h under 90 bar of H 2 pressure (Table 1, entry 26). The promoting effect of Fe on Cu catalyst performance was also studied by Manikandan et al [136]. Cu-Fe/Al 2 O 3 catalyst, with 10 wt% of Fe, exhibited an excellent activity that led to high furfural conversion (>93%) and FA selectivity (>98%) under mild reaction conditions ( Table 1, entry 27).…”
Section: Introductionmentioning
confidence: 84%
“…Recently,F e-Cu/g-Al 2 O 3 was reported to be an effective catalystw ith 93 %f urfural conversion and 98 %s electivity to furfuryl alcohol. [17] Manikandan and coworkers showedt hat Fe and Cu are fully reduced to metal, and bimetallic Fe-Cu was formed at 673 K, which was observedb yu sing in situ powder XRD. They also show that Fe was responsible for the highr eactivity,a nd the selectivity was driven by Cu.…”
Section: Introductionmentioning
confidence: 95%
“…The catalyst was calcined at 1123 K and then added directly into a batch reactor without any prereduction, and it is claimed that the acidic centers in these Cu‐Fe catalysts are the active sites for the dehydration of furfuryl alcohol to 2‐methylfuran. Recently, Fe‐Cu/γ‐Al 2 O 3 was reported to be an effective catalyst with 93 % furfural conversion and 98 % selectivity to furfuryl alcohol . Manikandan and coworkers showed that Fe and Cu are fully reduced to metal, and bimetallic Fe‐Cu was formed at 673 K, which was observed by using in situ powder XRD.…”
Section: Introductionmentioning
confidence: 99%
“…Through DFT and kinetic studies, it was suggested that the oxophilicity of Fe facilitated the adsorption of FA through a η 2 ‐(C,O) surface species, which drove the reaction towards hydrogenolysis of the C=O bond . Additionally, very recent studies conducted with Cu–Fe supported on carbon and silica also demonstrated a synergistic effect between the more oxophilic Fe species and the more reduced Cu species for hydrogenation and hydrogenolysis of FUR . Temperature‐programmed desorption (TPD) and high resolution electron energy loss spectroscopy (HREELS) under ultra‐high vacuum conducted on Pt–Zn catalysts suggested a similar mechanism, in which Zn acted as the oxophilic metal and allowed for a tilted adsorption mode to be more prevalent on the catalyst surface .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Additionally, very recents tudies conducted with Cu-Fe supported on carbon and silica also demonstrated as ynergistic effect between the more oxophilic Fe speciesa nd the more reduced Cu speciesf or hydrogenationa nd hydrogenolysis of FUR. [11,12] Te mperature-programmed desorption (TPD) and high resolution electron energy loss spectroscopy (HREELS) under ultrahigh vacuum conducted on Pt-Zn catalysts suggested as imilar mechanism, in which Zn acted as the oxophilicm etal and allowed for at ilted adsorption mode to be more prevalent on the catalyst surface. [13] Other vapor phase reactions have been conducted with multiple metal systemsi ncluding Cu-Zn-Al and Cu-Zn-Al-Ca-Na.…”
Section: Introductionmentioning
confidence: 99%